Languaging relations for transforming the literacy and language arts classroom - Beach, Richard; Bloome, David (Routledge, 2019)
"Applying a languaging perspective to literacy, this volume reframes the teaching and learning of language arts as social actions and generates new questions to make visible the social, cultural, psychological, and educational processes at the heart of the literacy and language arts. Chapter authors explore diverse aspects of a languaging framework--the perspective of language as a series of social actions and ongoing processes--and suggest directions for addressing substantive engagement as well as the marginalization, superficiality, and violence (symbolic and otherwise) that characterize the educational experience of so many students. Responding to the need to foster and support students' intellectual, social, and affective worlds, this book showcases how languaging relations among teachers and students can deepen interactions and engagement with texts, and enhance understandings of agency, personhood, power relations in order to transform literacy and language arts classrooms and improve the lives of teachers and students in educational settings"--